Hak Konstitusional Penyandang Disabilitas Dalam Pemilihan Umum: Analisis Pengawasan Administratif Pada Pemilu 2019 Di Kota Gorontalo - Alvian Mato; Siti Rahmawaty Igirisa (Al-Mizan (e-Journal), 2026)
This study analyzes the protection of the constitutional rights of persons with disabilities in the 2019 General Election in Gorontalo City through the perspective of administrative supervision. The research focuses on the role of the General Election Supervisory Agency (Bawaslu) in ensuring that electoral administration processes comply with legal provisions. Using an empirical juridical approach, this study examines supervisory practices across voter data updating, election socialization, polling station accessibility, and voting processes. Data were collected through interviews, observation, and documentation, and analyzed qualitatively. The findings indicate that administrative supervision was conducted in accordance with the regulatory framework of Bawaslu Regulation Number 21 of 2018 and was implemented across all electoral stages. However, several obstacles were identified, including the lack of continuous updating of disability voter data and limited accessibility factors affecting voter turnout. Although supervisory mechanisms functioned effectively in ensuring procedural compliance, they have not fully guaranteed the optimal fulfillment of constitutional rights of persons with disabilities in practice.